A comprehensive review on bio-hydrogen production from brewery industrial wastewater and its treatment methodologies. (1st July 2022) - Aravind Kumar, J.; Sathish, S.; Krithiga, T.; Praveenkumar, T.R.; Lokesh, S.; Prabu, D.; Annam Renita, A.; Prakash, P.; Rajasimman, M.
Graphical abstract: Highlights: Recognize the significance of converting industrial effluent into valuable products. Potentials for producing bio-hydrogen from brewery industrial effluent are included. Methodologies for comprehensive Brewery Industrial Effluent Treatment are discussed. Reciprocal mechanism of aerobic/anaerobic treatment of brewery effluent is discussed. Physical-chemical factors are identified as essential factors in bio-gas production" Abstract: The brewing process for beer extraction often produces a maximum quantity of wastewater and solid waste materials. It needs to be properly discarded in a cost-effective and safe mode to reach the standard discharge regulations laid down by governmental agencies to conserve human/animal life in the environment. It is clearly understood that ten litres of potable water were required for brewing a litre of beer. Furthermore, brewery wastewater, effluent obtained in enormous quantities from agriculture-based industries and its treatment technique can be merged with energy generation strategies as in the case of biogas formation, effluent rich in either Hydrogen (H2 ) or methane (CH4 ) content. Thus, the methane production via anaerobic co-digestion of such brewing waste is well recognised. In contrast, biosynthesis of H2 has been analysed for certain agro-based wastewaters but has obtained less focus in the case of brewing water. Hence, the in-depth review presents sources for a generation and complete decomposition of the brewing water, enlightening the recent research concerning methane production by anaerobic digestion. Also highlighted are the optimum conditions for H2 generation from wastewater sources emanating due to agriculture. This article highlights the complete analysis of current trends in brewing wastewater treatment techniques and their potential benefits for reuse based on recent findings. The key issues have also been addressed for brewing wastewater treatment and its reuse strategy, highlighting future social benefits recommendations.